PENGARUH PUPUK ORGANIK KOTORAN SAPI TERHADAP PERTUMBUHAN NYAMPLUNG (Calophyllum inophyllum Linn) PADA TANAH ULTISOL - Raiwani, Rumiati; burhanuddin, .; Darwati, Herlina (JURNAL HUTAN LESTARI, 2016)
The research on the effect of organic fertilizer of cow dung on the growth of nyamplung (Calophyllum inophyllum Linn) on Ultisol, aims to determine the effect of fertilization on seedling the growth of nyamplung seedling using organic fertilizer of Cow dung, and to abtain the best comparison between Ultisol soil and organic fertilizer of cow dung. The method used in this research was an experimental method with a completely randomized design (CRD). The experiment design consisted of 6 fertilization treatments and each was repeated 5 times, the number of seed used in the research was 30 nyamplung plant seeds. The results showed that the edition of organic fertilizer of cow dung in the planting medium of Ultisol soil provided better results on the nyamplung plant growth especially the growth in high, diameter, number of leaves and dry weight than only using PMK (Red Yellow Podsolik ) soil. The best growth of nyamplung plant was the addition of organic fertilizer of cow dung in the treatment at a ratio of 1: 5 (K5 compared with no treatment (control) and other treatments. Keywords : Calophyllum inophyllum, Fertilization, Growth, Nyamplung, Ultisol.